Content- and Language-Integrated Learning-Based Strategies for the Professional Development of Early Childhood Education Pre-Service Teachers - Alvira, Roberto; González, Yady (Íkala, Revista de Lenguaje y Cultura, 2018)
This research article presents the results of an exploratory study that was conducted with a group of 14 early childhood education pre-service teachers at a private Colombian university. It intended to determine: 1) the amount of metalanguage expressions used for teaching English as a foreign language (EFL) and foreign language (FL) content; 2) the number of concepts related to the teaching of EFL and FL content pre-service teachers were able to learn in a 7-session (14 face-to-face hours) course based on a methodology inspired by the content and language integrated learning (CLIL) approach, using songs, rhymes, and poems in English; 3) the degree of difficulty pre-service teachers perceived about teaching English and English content to young children. This quasi-experimental study was performed with pre- and post-study tests given to one group, analyzing quantitative data through a non-parametric statistical hypothesis test and a non-parametric measure of rank correlation. Pre-service teachers were found to successfully learn vocabulary and concepts, but their perceptions about the degree of difficulty of teaching EFL and FL content remained basically the same as prior to the course. In addition, the correlation between the participants’ level of English and their learning process was analyzed, as well as the correlation between English proficiency level and perception of the degree of difficulty of teaching EFL and FL content. The results show a strong correlation in the first case, but no correlation for the second one.